Prevalence of testing and coronavirus-19 among nurses in the pandemic - Gilmara Holanda da Cunha; Larissa Rodrigues Siqueira; Marina Soares Monteiro Fontenele; Lavna Albuquerque Moreira; Ane Kelly Lima Ramalho; Francisco Vagnaldo Fechine (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To determine the prevalence of testing and COVID-19 among nurses during the pandemic in the State of Ceará. Method: A cross-sectional study with 379 nurses, through a network sampling technique, using a sociodemographic, labor, and clinical questionnaire. The study performed a descriptive statistics, univariate and multivariate logistic regression analysis. Results: The prevalence of testing and COVID-19 were, respectively, 63.3% and 25.0%. The most common symptoms were anosmia, ageusia, and myalgia. There was inadequate use of personal protective equipment due to material shortage. The odds ratio for COVID-19 was higher in those with children, people with diabetes, from the capital, with more than two jobs, in hospital and emergency room, and from the frontline. In the multivariate logistic regression, nurses with children (p=0.011), diabetics (p=0.018) and frontline (p<0.001) had more chances for COVID-19. Conclusion: Expanded testing, ongoing in-service education, and adequate personal protective equipment are needed to improve nurses' work.